2014
DOI: 10.1038/ncomms6538
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic memory of the first cell fate decision prevents complete ES cell reprogramming into trophoblast

Abstract: Embryonic (ES) and trophoblast (TS) stem cells reflect the first, irrevocable cell fate decision in development that is reinforced by distinct epigenetic lineage barriers. Nonetheless, ES cells can seemingly acquire TS-like characteristics upon manipulation of lineage-determining transcription factors or activation of the extracellular signal-regulated kinase 1/2 (Erk1/2) pathway. Here we have interrogated the progression of reprogramming in ES cell models with regulatable Oct4 and Cdx2 transgenes or condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 64 publications
(97 reference statements)
11
82
0
Order By: Relevance
“…This sensitivity of TSCs to precise TF stoichiometries is a likely reason for the significant spontaneous differentiation rates commonly observed in TSC cultures. It may also explain why reprogramming strategies based on overexpression or activation of selected TFs specifically between ESCs and TSCs have proved difficult and tend to result in loss of self-renewal potential and terminal differentiation (Niwa et al 2000(Niwa et al , 2005Ralston et al 2010;Cambuli et al 2014). In the bigger picture, this precarious balance might explain why derivation and maintenance of TSCs are difficult and have often proved inefficient or even unsuccessful from other species, in particular humans (Kunath et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensitivity of TSCs to precise TF stoichiometries is a likely reason for the significant spontaneous differentiation rates commonly observed in TSC cultures. It may also explain why reprogramming strategies based on overexpression or activation of selected TFs specifically between ESCs and TSCs have proved difficult and tend to result in loss of self-renewal potential and terminal differentiation (Niwa et al 2000(Niwa et al , 2005Ralston et al 2010;Cambuli et al 2014). In the bigger picture, this precarious balance might explain why derivation and maintenance of TSCs are difficult and have often proved inefficient or even unsuccessful from other species, in particular humans (Kunath et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TFs were cloned and sequence-verified. All transformations to yield stable cell lines were performed in the TS-EGFP cell line, which exhibits proven placental contribution competence (Tanaka et al 1998;Cambuli et al 2014). …”
Section: Stem Cell Culturementioning
confidence: 99%
“…We hypothesize that transcriptional or epigenetic mechanisms could regulate CDX2 activity in naïve and primed pluripotent stem cell types. Interestingly, ESC-derived TSClike cells fail to acquire genomic methylation features of TSCs [21], arguing that epigenetic differences between ESCs and EpiSCs could limit the developmental potential of EpiSCs to become TSCs. Differences in the transcriptomes, proteomes, and chromatin states of ESCs and EpiSCs have been compared [62][63][64][65].…”
Section: Figmentioning
confidence: 99%
“…Knowledge of signaling pathways and transcription factors that reinforce these three lineages in the blastocyst has pointed to ways to alter the developmental potential of the stem cell lines derived from the blastocyst's lineages. For example, ESCs can be converted to TSCs by overexpressing the TE-specific transcription factor CDX2 in TSC medium [16] and by other means [17][18][19][20][21]. Importantly, overexpression of Cdx2 in ESCs leads to TSC-like cells with highly similar morphology, developmental potential, and gene expression as embryoderived TSCs [16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of which other factor/s are repressed by miR-34a, which are important players in Gata2-mediated activation of MERVL (and in achieving a bi-potential phenotype) upon miR-34a de-repression. It has been shown that several gatekeepers such as Elf5 safeguard ESCs from transdifferentiating into trophoblast stem cells (TSCs, TE equivalent) by a mechanism involving methylation [9]. Thus, other intriguing questions are whether the methylation status of these gatekeepers is deregulated in miR-34a -/-pluripotent stem cells, and whether completely reprogrammed transdifferentiated-TSCs can be attained in miR-34a -/-pluripotent stem cells, without genetic manipulations.…”
mentioning
confidence: 99%